Making and making use of a baseline: botanical research and the legacy of Chico Mendes - Daly, Douglas Charles; Silveira, Marcos; Obermüller, Flávio Amorim (Desenvolvimento e Meio Ambiente, 2018)
The vision and charisma of Chico Mendes made Acre a destination for many people fascinated and inspired by the great socio-environmental experiments he was proposing; his murder only increased that interest. The extractivist movement engendered by Chico Mendes, with a potentially strong role for basic research, was the primary reason that The New York Botanical Garden (NYBG) committed scientists and resources in order to study the flora of Acre and Southwestern (SW) Amazonia. At the outset of our collaborative agreement with the Universidade Federal do Acre (UFAC)[Federal University of Acre], Acre was botanically one of the least-known parts of Amazonia. Thirty years later, it has come to be one of the best-known parts, due in great part to the First Catalogue of the Flora of Acre, Brazil, which contributed with the first ten percent of the checklist to the flora of all Brazil. More importantly, we were able to add original data to arguments for the making of new protected areas in Acre. In these process, we established Acre as a point of reference for botanical knowledge about Southwestern Amazonia. The NYBG/UFAC partnership was an early participant in the MAP (Madre de Dios-Acre-Pando) consortium and helped designate priorities portions of SW Amazonia to conservation. Our botanical research in this region has emphasized potential applications to resource management. Most recently, our efforts have focused on reforming forest management and monitoring by continuing to build on our baseline of knowledge of the flora, proposing better protocols for sampling and collection in forest inventories, offering training courses to the certification of new generations of “master woodsmen”, and developing tools and resources for tree identification. Our capacity-building efforts now focus primarily on communities situated in or close by protected areas, treating them as participants and collaborators in forest inventory and monitoring. Making good use of traditional knowledge and focusing on forest communities as full participants and partners in projects devoted to inventory, management, monitoring and conservation of forests throughout Amazonia, we are doing our small part to honor the legacy of Chico Mendes.